The Influence of Ethics Training and Human Resource Competence on Ethical Culture and its Impact on Employee Performance - Suhendrawan Suhendrawan; Dian Indiyati (Eduvest - Journal of Universal Studies, 2025)
Fluctuating employee performance and rising ethics violations have become critical challenges at PT Amman Mineral Nusa Tenggara, highlighting the need to strengthen ethical culture and human resource competence. Although ethics training programs have been implemented, participation remains below target, and performance inconsistencies persist. This study aims to examine the influence of ethics training and human resource competence on ethical culture and their combined effect on employee performance. A quantitative approach was employed, using data from 307 employees gathered via structured questionnaires. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that ethics training and human resource competence significantly and positively influence ethical culture. In turn, ethical culture has a substantial impact on employee performance. Additionally, ethics training and human resource competence also exert a direct effect on performance outcomes. These results confirm that building a strong ethical culture supported by effective training and competent human capital is essential for improving organizational productivity. The implications of this study suggest that companies, especially in high-risk industries like mining, must prioritize integrated ethics and competency development strategies to foster sustainable employee performance and ensure alignment with corporate values and compliance expectations.